ADAPTASI PEMBELAJARAN ONLINE DENGAN TINGKAT KECEMASAN PADA ANAK USIA SEKOLAH SELAMA MASA PANDEMI DI SDN 2 KOTA BARAT - Leny Ali; Nur Uyuun I. Biahimo; Rahmawati Ibrahim; Nazli Alamri (Jurnal Rumpun Ilmu Kesehatan, 2021)
Online learning is carried out as a form of health protocol in order to inhibit the spread of the corona virus. The method is descriptive correlation type, cross sectional study approach. The populations were all the students in grades V and VI of SDN 2 Kota Barat, amounting to 66 people. With the Total Sampling technique. The results showed most of the school-age children at SDN 2 Kota Barat had a high category of online learning adaptation and experienced mild anxiety. The relationship between online learning adaptation and anxiety levels in school-age children during the pandemic at SDN 2 Kota Barat. Children who have been able to adapt well have also indirectly succeeded in reducing the anxiety they face during the teaching and learning process. It is recommended for nursing students not only to focus on studies related to health and nursing, but also to examine the world of education which of course is related to health problems